Isu Lingkungan dalam Perspektif Kalam, Fiqh, dan Tasawuf - Sukarni, Sukarni (ISLAMICA: Jurnal Studi Keislaman, 2013)
There is no doubt that the problem of environment has become the most formidable issue faced by human being in the modern history. The danger imposed by the environmental crisis is much greater than the danger of any forms of war. This crisis has thus become the greatest enemy of humanity. The level and extent of the danger requires equally a great effort to address and tackle it. It is here that this paper tries to contribute. It attempts to offer an Islamic perspective of environment and its conservation. The paper is convinced that Islam is rich with perspectives on this issue. It therefore, introduces the many theories and views on environment that the sciences of Islam have spoken about. It brings into discussion the view of the science of theology (kalam), jurisprudence (fiqh) and sufism Â (tasawuf) on environment. Each of these sciences is discussed in relation to the others, as well as in the context of what the paper calls fiqh lingkungan (the jurisprudence of environment). The idea that underlines the paper is thatthese sciences areâgenerally speakingâconcerned with the idea of personal and collective responsibility; an idea that already has a direct relevance to the problem of environment.